Spatial association of biosocial and economic factors with reproductive women obesity in urban India - Priya Das; Subhadeep Saha; Tanu Das; Partha Das; Tamal Basu Roy (PLoS ONE, 2025)
Obesity creates several health complications among the urban women from reproductive age group. So far it is most ignored public health concern particularly in Indian context. The study aims to focus on the identification of cluster of districts with obese urban women and its spatial association with selected spatial determining explanatory factors.This study utilized secondary data obtained from the fifth round of the National Family Health Survey (NFHS-5), 2019-2021.The study performed spatial cluster of districts through univariate Moran’s I and its association with selected determining factors through bivariate Local Indicator of Spatial Association (BiLISA). Geographically Weighted Regression (GWR) was applied to measure the magnitude of independent factors over the space affecting the prevalence of outome of urban obese women.The spatial autocorrelation value of obesity among the urban women was found 0.429, depicting the moderate concentration of obesity coverage among the urban women over the districts of India. The results of bivariate LISA revealed that the highest bivariate Moran’ I value among all the predictors were identified for those women who had caesarean delivery (I = 0.274), followed by non-poor population (I = 0.208). The adjusted R2 value evidenced by the GWR model was 0.727 indicated that the employed explanatory variables was explaining about 73% for making influence on the prevalence of obesity among urban women of reproductive age group across the districts of India. This study recommends for an urgent need of interventions of the target areas focusing predominantly the urban women belonging from higher socio-economic status.